X-chromosome inactivation and escape - DISTECHE, CHRISTINE M. (J Genet, 2015)
X-chromosome inactivation, which was discovered by Mary Lyon in 1961 results in random silencing of one X chromosome in female mammals. This review is dedicated to Mary Lyon, who passed away last year. She predicted many of the features of X inactivation, for e.g., the existence of an X inactivation center, the role of L1 elements in spreading of silencing and the existence of genes that escape X inactivation. Starting from her published work here we summarize advances in the field.